1999
DOI: 10.1093/hmg/8.1.81
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome 4p haplotype segregating with Parkinson's disease and postural tremor

Abstract: We investigated a large family with levodopa-responsive, Lewy body parkinsonism in which the disease segregates as an apparent autosomal dominant trait. After performing a genome screen, we identified a chromosome 4p haplotype that segregates with the disease. However, this haplotype also occurs in individuals in the pedigree who do not have clinical Lewy body parkinsonism but rather suffer from postural tremor, consistent with essential tremor. These data demonstrate a new locus for Lewy body parkinsonism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(126 citation statements)
references
References 29 publications
3
118
0
5
Order By: Relevance
“…These observations suggest that HTRA2 has a causal role in essential tremor and in the subset of Parkinson disease preceded by essential tremor. Among essential tremor patients generally, the incidence of Parkinson disease is increased four-to fivefold, and essential tremor and Parkinson disease have been observed in the same families (33)(34)(35). We speculate that casecontrol studies of that subset of Parkinson disease preceded by essential tremor would reveal associations with functional missense alleles of HTRA2.…”
Section: Discussionmentioning
confidence: 84%
“…These observations suggest that HTRA2 has a causal role in essential tremor and in the subset of Parkinson disease preceded by essential tremor. Among essential tremor patients generally, the incidence of Parkinson disease is increased four-to fivefold, and essential tremor and Parkinson disease have been observed in the same families (33)(34)(35). We speculate that casecontrol studies of that subset of Parkinson disease preceded by essential tremor would reveal associations with functional missense alleles of HTRA2.…”
Section: Discussionmentioning
confidence: 84%
“…The causative gene has not yet been identified for all of the loci, nor do all of the identified genes contain causative or disease-determining mutations (i.e., variations in some of these genes are considered genetic risk factors increasing the risk to develop PD rather than being a sufficient cause). Finally, one locus, PARK4, was designated as a novel chromosomal region associated with PD (Farrer et al 1999;Singleton et al 2003) but was later found to be identical with PARK1 (SNCA-associated PD) (Singleton et al 2003). It is noteworthy that some of the loci have been identified by genetic linkage analysis in large families, some based on the known function of the protein product of the gene they contain, yet others have been established by genomewide association studies performed on a population level.…”
Section: Genetic Classification Of Pdmentioning
confidence: 99%
“…This locus on chromosome 4p14-16.3 was described in 1999, in six generations family with early-onset autosomal dominant, rapidly progressive and levodopa-responsive PD with atypical features more like as Lewy body disease [56] manifesting segregation with essential tremor and sharing the same haplotype. The triplication of the locus containing α-synuclein [57] correspond au locus PARK1.…”
Section: Park4mentioning
confidence: 99%